Reading of Religious Text - karbia, Karima Mohamed (Journal of Humanities & Social Sciences, 2020)
The religious text today became the axis of the work of many Arab modernists, such as Arkoun, Jabri, Abu Zeid and Abdul Majeed Al Sharafi... and others, which resulted in what is known as the modernist readings of the religious text, which sees the standards of our era and the needs of the Arab individual demand moving from the Court of duplication to resort to the court of reason. From the culture of certainty to the culture of questioning and doubt, and from the culture of absolute truth to the culture of relativity, and out of this idea, the modernists began their view of the Holy Qur’an as a narrative product that can be reproduced and read in accordance with the various literary criticisms in the study of literary and historical texts. such as methods of the human and social sciences and the comparative history of religions. Which contributes to the destabilization of all the buildings of the sanctuary built by the traditional theological mind, and thus works to empty the religion from its ideological content and determine its area within the framework of secular systematic. The reading of the text accordingly becomes a cultural linguistic event and therefore there is no absolute historical fact because the absolutism deviates from the will of man. This kind of reading was also an invitation to the realization of the rationality of pluralism, not the rationality of status. and the call for openness to humanity and cosmic culture. But the prospects for this theory remain limited in practice. These contemporary readings have benefited from the Western approaches applied in human texts, philosophical and literary..